IL-1Ra Protects Hepatocytes from CCl4-Induced Hepatocellular Apoptosis via Activating the ERK1/2 Pathway - Ying Zheng; Xinyi Xiao; Zhuoyi Yang; Meiqi Zhou; Hui Chen; Siyi Bai; Jianwei Zhu; Yunsheng Yuan (Georg Thieme Verlag KG, 2020)
Interleukin-1 receptor antagonist is an important acute-phase protein and an immune mediator, and its expression is associated with the development of hepatitis or acute liver failure. The aim of this study was to investigate whether recombinant human interleukin-1 receptor antagonist directly targets and improves cell survival in a carbon tetrachloride-induced hepatocyte injury model in vitro. A human hepatoma cell line and a mouse hepatocyte cell line were used to establish carbon tetrachloride-induced cell injury models in vitro, and cell viability, apoptosis, and reactive oxygen species level were determined to assess the degree of hepatocellular damage. Quantitative real-time polymerase chain reaction was used to analyze the level of interleukin-1β, interleukin-6, and tumor necrosis factor-α mRNA in cells; extracellular regulated protein kinases 1/2 phosphorylation in hepatocytes was analyzed using western blotting. Recombinant human interleukin-1 receptor antagonist could directly target hepatocytes, improve cell survival, and decrease carbon tetrachloride-induced cell apoptosis in vitro. In hepatocytes, recombinant human interleukin-1 receptor antagonist remarkably downregulated expression of interleukin-1β, interleukin-6, and tumor necrosis factor-α in hepatocytes exposed to carbon tetrachloride. It also decreased accumulation of reactive oxygen species and abrogated the suppression of extracellular regulated protein kinases 1/2 phosphorylation induced by carbon tetrachloride. However, stimulation of cells with an extracellular regulated protein kinases 1/2 inhibitor blocked the recombinant human interleukin-1 receptor antagonist-induced upregulation of extracellular regulated protein kinase1/2 activation and abrogated the improvement in hepatocyte survival following carbon tetrachloride treatment. Collectively, these findings provide new insights into the hepatocyte-protective mechanism of recombinant human interleukin-1 receptor antagonist.